The behavior of Islamic and conventional banks around the pandemic: Cross-country evidence - Saibal Ghosh (Islamic Economic Studies (IES), 2023)
Purpose - Using cross-country data on the 1,000 largest global banks for 2019, the paper aims to examine the response of bank risk and returns to the pandemic. Design/methodology/approach - The author employs weighted least squares (WLS) techniques for the purposes of analysis. Findings - The findings suggest that banks with Islamic windows increased their riskiness in response to the pandemic, although there was not much impact on profitability. Additionally, the author categorizes banks based on certain major characteristics and find that these findings are manifest primarily for well-capitalized and less liquid banks. Originality/value - Research as to the impact of the pandemic on banks' balance sheets has been an unaddressed area of research. By focusing on a large sample of banks across countries with both Islamic and conventional banking presence, the analysis sheds light on the balance sheet response of banks to the pandemic, an aspect that has not been addressed earlier.
Keywords: G21; G28; 330; Banking; Islamic; Islamic windows; Profitability; Risk; Weighted least squares